Body mass composition analysis as a predictor of overweight and obesity in children and adolescents - Aniśko, Bartosz; Siatkowski, Idzi; Wójcik, Małgorzata (Frontiers in Public Health, 2024)
Introduction Body mass composition is directly related to health and its disorders are correlated with diseases such as obesity, diabetes, osteoporosis and sarcopenia. The purpose of this study was to analyze body mass composition among traditional elementary school students and ballet school students. Methods A total of 340 students participated in the study, 95 of whom attended ballet school and 245 elementary school students. A Tanita BC-418 MA analyzer was used to analyze body mass composition. Such body composition indices as BMI (Body Mass Index), muscle mass, fat mass, lean body mass and water content were evaluated. Results The results show statistical significance for BMI between high school ballet students and elementary school ballet students, as well between high school ballet students and elementary school students. Comparisons in relation to gender and schools BMI, statistical significance was obtained for: BHSw (ballet high school women) and EBSw (elementary ballet school women), BHSw and ESw (elementary school women), BHSm (ballet high school men) and EBSm (elementary ballet school men), and between BHSm and ESw. Comparing muscle mass index (kg) between ballet high school and elementary school, between ballet high school and elementary school, and between ballet high school and elementary school - statistical significance was obtained for all comparisons. Analyzing in pairwise comparisons by gender and school achieved a statistically significant difference for: BHSw and EBSw, BHSm and EBSw, EBSw and ESm. Comparing the fat mass index (kg), no significant differences were observed between the analyzed schools and the school and gender of the children studied. The value of the lean body mass index differed significantly between groups by school and gender. Comparing the water content index, statistically significant differences were obtained for school and gender. Discussion The body mass composition of ballet school students differs from that of standard school students.